Magic mistakes! - Ryan, Margaret, 1944-; Murfin, Teresa (New York : Barron's, 2006)
Fairy is determined to do well in cooking class, but with Scary Fairy around to stir up trouble, things are bound to go wrong once again.
Keywords: Fairies -- Juvenile fiction; Cooking -- Juvenile fiction